2014
DOI: 10.1186/1472-6882-14-306
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation on cytochromes P450 in rat mediated by total alkaloid extract from Corydalis yanhusuo

Abstract: BackgroundYanhusuo (Corydalis yanhusuo W.T. Wang; YHS), is a well-known traditional Chinese herbal medicine, has been used in China for treating pain including chest pain, epigastric pain, and dysmenorrhea. Its alkaloid ingredients including tetrahydropalmatine are reported to inhibit cytochromes P450 (CYPs) activity in vitro. The present study is aimed to assess the potential of total alkaloid extract (TAE) from YHS to effect the activity and mRNA levels of five cytochromes P450 (CYPs) in rat.MethodsRats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Incubation was done according to the previously described approach 20. The incubation mixtures (200 µL) included 100 mM potassium phosphate buffer (pH 7.4), 0.5 mg/mL mice microsomal protein, and mixture probe substrates for CYP450s (10 µM phenacetin for CYP1A2, 100 µM tolbutamide for CYP2C19, 2.5 µM dextromethorphan for CYP2D6, 20 µM chlorzoxazonefor CYP2E1, 5 µM midazolam for CYP3A4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation was done according to the previously described approach 20. The incubation mixtures (200 µL) included 100 mM potassium phosphate buffer (pH 7.4), 0.5 mg/mL mice microsomal protein, and mixture probe substrates for CYP450s (10 µM phenacetin for CYP1A2, 100 µM tolbutamide for CYP2C19, 2.5 µM dextromethorphan for CYP2D6, 20 µM chlorzoxazonefor CYP2E1, 5 µM midazolam for CYP3A4).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we have reported a rapid LC–MS/MS method for determination of the activities of five CYP450s in the rat liver 20. Briefly, the HPLC system consisted of an LC-20 AD pump, a DGU-20 A3 degasser, a SIL-20AC autosampler, and a CTO-20A column oven (Shimadzu, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…It also bioactivates several procarcinogens and protoxins, including N-nitrosodimethylamine, benzene, and carbon tetrachloride, to their reactive intermediates [27] . CYP2E1 generates reactive oxygen species (ROS) and substrate-derived radicals, such as oxygen and hydroxyl radicals, which can mediate lipid peroxidation, protein inactivation and DNA damage, leading to cellular injury, especially in the presence of CYP2E1 inducers [28] . Several clinical disorders are associated with changes in the regulation of CYP2E1 and its consequent abnormalities, which include alcoholic liver disease, carcinogenesis, hepatocellular and cholestatic injury, among others [29] .…”
Section: Wwwnaturecom/aps Liu L Et Almentioning
confidence: 99%
“…CYPs are the mixed function oxidase system mainly existing in the liver, and play roles in the metabolism of over 80% drugs [13]. Induction or inhibition of CYP450 is implicated in traditional medicine-induced hepatoprotection and/or hepatotoxicity [14][15][16]. CYP450 genes are regulated by corresponding nuclear receptors, their coordinate regulation affects hepatic phase I and phase II metabolisms [17].…”
Section: Introductionmentioning
confidence: 99%